Antioxidative Activities of Selected Malaysian Herb Extracts during Accelerated Oxidation Test and Deep- Fat Frying - Mohd Nor, Fatihanim (2008)
The potential use of selected Malaysian herb (Murraya koenigii, Curcuma longa, Citrus hystrix and Pandanus amaryllifolius) leaf extracts as natural antioxidant were evaluated in antioxidant assay, accelerated oxidation test and deep fat frying. They were analyzed for antioxidant activity using 1-1-diphenyl-2-hydrazyl (DPPH) radical- scavenging activity assay and linoleic acid model system. The extracts at different concentrations were added to refined, bleached and deodorized (RBD) palm olein and heated to frying temperature, analyzed for peroxide value, anisidine value, free fatty acid and oxidative stability index (OSI). From there, optimum concentration was chosen and 40 hr frying experiment was being carried out. The polyphenol content ranged from 101.4 mg in P. amaryllifolius to 116.3 mg C. longa. The antioxidative activity of the extracts in both assays followed the decreasing order of: C. longa> M. koenigii> C. hystrix> P. amaryllifolius. 2000 ppm was chosen as the optimum concentration to be used in deep frying experiment. Extracts of Pandanus amaryllifolius and Citrus hystrix exhibited protective activity towards RBD palm olein that was comparable to BHT (p>0.05) during frying. The extracts were useful in improving and also maintaining the sensory characteristics of French fries. The French fries treated with herb extracts were acceptable by panelists until day 5 of frying. The natural antioxidants significantly (p<0.05) lowered the rate of oil oxidation during deep- fat frying and maintaining the quality of French fries. They exhibited excellent heat- stable antioxidant properties are good natural alternative to existing synthetic antioxidants for the food industry.